The Evaluation of Table Tennis Development Program in Student Sports Training Centre Jakarta - Erwin Sofan; Yasep Setiakarnawijaya; Abdul Gani (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to evaluate the table tennis athlete coaching program at Student Sports Training Centre Jakarta. This study uses the CIPP evaluation model (context, input, process and product) was developed by Stufflebeam. The data collection method used triangulating data such as: questionnaires, observations and documentation related to the research topic. The research method used is descriptive qualitative with respondents’ they are: coaches, athletes and management of Student Sports Training Centre Jakarta at table tennis branch. The results of this study indicate that: 1) context : strategies at Student Sports Training Centre Jakarta are clear and well understood by athletes and coaches: 2) inputs : the recruitment system for athletes and coaches has been structured and also Jakarta has good facilities and well maintained 3) process: training and evaluation programs have been well prepared by the coach, all the athletes must be enthusiasm and discipline to do all the programs 4) product: the achievements of athletes, individually and in groups should be as a main concern for further improvement. Thus, the athletes need to improve the achievements of the athletes, both individually and in teams or groups in national and international competitions.